Thermal Characterization of Pozzolanic Activity of Hydrated Cement System Modified by Silica Based Industrial Waste - Faatima Zahra, Ahmat Asim; Norsuzailina, Mohamed Sutan (JASPE, 2015)
This study investigates the potential of using silica based industrial waste specifically waste calcined clay (WCC) from ceramic industry as partial cement replacement. Pozzolanic activity characterization was done by using thermal and mechanical characterization techniques namely Thermal Gravimetric Analysis (TGA) and Compressive Strength Test (CS), respectively. Finely grounded waste vase of varying particles sizes range from less than 75m, 75m and 150m were used as 10%, 20%, and 30% cement replacements with 0.45 water to cement ratio (w/c). First, progression of CS from day 1 to 28 of WCC modified mortar and unmodified cement mortar (UCM) was monitored as an indirect indication of pozzolanic activity. It was found that 75WCC10% performed higher 28 day compressive strength compared to unmodified cement mortar (UCM). To further confirm the result, TGA characterization of Calcium Silicate Hydrate (C-S-H) and Calcium Hydroxide (CH) as pozzolanic activity indicator was done on WCC modified cement pastes in comparison to unmodified cement paste (UCP). TGA analysis has shown the pozzolanic activity indicated by the decrease of CH and the increase of C-S-H in WCC modified cement paste. Based on this study, WCC possesses pozzolanic characteristic which is the main criteria to be qualified as an effective material as partial cement replacement.